Cobalt(VI)-oxo species-mediated selective oxidation of electron-rich organic contaminants by Co-loaded hydroxylated g-C3N4 with high resistance to an inhibitory effect of background constituents - Lee, Youn Jun; Son, Chae Young; Jeong, Yoo Jae; Cho, In Sun; Park, Seong Jik; Lee, Chang Gu (Applied Surface Science, 2024)
Understanding of the selectivity of high-valent cobalt-oxo species (Co(IV)[dbnd]O) toward diverse organic pollutants with different characteristics in the presence of background constituents remains limited. Here, we prepared Co-loaded hydroxyl group-grafted graphitic carbon nitride (Co-OHCN) using a facile method for the effective formation of Co(IV)[dbnd]O. The role of the hydroxyl group in anchoring Co ions was investigated using several characterization methods (TEM, XRD, FT-IR, and XPS). Co-OHCN exhibited superior efficiency in degrading 4-chlorophenol (4-CP) (98.0 % ± 0.3 %) within 15 min of peroxymonosulfate (PMS) activation reaction. In the Co-OHCN/PMS system, Co(IV)[dbnd]O had the highest steady-state concentration ([Co(IV)[dbnd]O] = 1.40 × 10−10 M), significantly exceeding that of other reactive oxygen species (ROS) ([SO4[rad]−] = 9.22 × 10−13 M, [[rad]OH] = 1.82 × 10−13 M). The dominant role of Co(IV)[dbnd]O in 4-CP degradation was further revealed through scavenger tests, probe methods, and electrochemical analysis. Additionally, the anti-interference of Co(IV)[dbnd]O in the degradation of electron-rich organic substrates to background constituents (NOM and halide ions) was systemically validated using three organic pollutants with different ionization potential values (diclofenac, 4-CP, and benzoic acid). This study provides insight into an efficient strategy for Co(IV)[dbnd]O -mediated pollutant elimination and organic substrate-dependent selectivity of Co(IV)[dbnd]O during water decontamination.
Keywords: 4-chlorophenols; Anti-interference; Cobalt-oxo species; Electron-rich; Hydroxyl groups; Organic contaminant; Organic substrate; Oxo species; Persulfate activations; Selective oxidation; Anti-interference; Cobalt-oxo species; Ionization potential; Persulfate activation